ERCC1 polymorphism and its expression associated with ischemic stroke in Chinese population - Deng, Xiao-Dong; Ke, Jian-Lin; Chen, Tai-Yu; Gao, Qin; Zhao, Zhuo-Lin; Zhang, Wei; Liu, Huan; Xiang, Ming-Liang; Wang, Li-Zhen; Ma, Ying; Liu, Yun (Frontiers in Neurology, 2023)
Background Excision repair cross-complementing group 1 (ERCC1) was considered a potential candidate gene for ischemic stroke, and its polymorphisms might be associated with the susceptibility to ischemic stroke. Methods A total of 513 patients with ischemic stroke and 550 control subjects were recruited. The expression levels of ERCC1 messenger RNA (mRNA) in peripheral blood mononuclear cells and its protein in plasma were detected by quantitative real-time PCR (qPCR) and enzyme-linked immunosorbent assay (ELISA), respectively. Rs3212986 polymorphism of ERCC1 was detected by PCR-restriction fragment length polymorphism (RFLP-PCR) and was confirmed by sequencing. The association between the ERCC1 rs3212986 polymorphism or its expression and ischemic stroke was further analyzed. Results The ERCC1 mRNA level in patients with ischemic stroke was lower than that in the control group (P < 0.05). However, the ERCC1 protein level in patients with ischemic stroke was higher than that in the control group (P < 0.05). The A allele of rs3212986 was associated with increased ischemic stroke risk (OR = 1.287, 95% CI = 1.076–1.540, P = 0.006). The association between rs3212986 polymorphism and ischemic stroke susceptibility was found in both recessive (OR = 2.638, 95% CI = 1.744–3.989, P < 0.001) and additive models (OR = 1.309, 95% CI = 1.028–1.667, P = 0.031), respectively. Similar results were obtained in the recessive model (OR = 2.015, 95% CI = 1.087–3.704, P = 0.026) after adjusting for demographic information and other variables. Additionally, the level of ERCC1 mRNA in the CC/CA genotype was higher than that in the AA genotype (P < 0.05). Conclusion It was suggested that the ERCC1 rs3212986 polymorphism was associated with ischemic stroke susceptibility in a Chinese Han population and that an A allele of rs3212986 was related to increased ischemic stroke risk. The altered ERCC1 expression level caused by the rs3212986 polymorphism might participate in the pathophysiological process of ischemic stroke.